Hubungan penggunaan IUD (intrauterin device) dengan pola aktivitas seksual pada perempuan di Kota Kupang - Koheresto G. Liufeto; Abdul Wahab; Ova Emilia (Berita Kedokteran Masyarakat (BKM), 2017)
The use of intra uterine device (IUD) and sexual activity patterns in women in KupangPurposeThe purpose of this study was to know the influence of intra uterine device type contraceptive use to the pattern of sexual activity.MethodsThis research was an observational study with a cross-sectional design using questionnaires to collect data. The samples were 190 women of fertile age in the city of Kupang. The correlation of intra uterine device usage and sexual activities pattern was analyzed by using chi square tests, and continued with multivariate analysis using logistic regression tests, using confidence interval (CI) of 95% and a level of significance of p<0.05.ResultsThere was no significant difference in patterns of sexual activities of women using intra uterine device with those who were not using contraception. The variables that were statistically significant were age, parity, duration of marriage and effects of intra uterine device use. Meanwhile variables that were not statistically significant were working status and duration of intra uterine device use.ConclusionThe usage of intra uterine device contraception did not affect patterns of sexual activities of women in Kupang. However, the effect of intra uterine device usage did have influence toward sexual activity, but such effect would be reduced over time up to 1 year of using. The recommendations given in this research is that it is necessary to further analyze intra uterine device usage effects toward sexual activities patterns.